Potensi Sumber dan Sebaran Sampah Laut di Ekosistem Terumbu Karang Perairan Pulau Kelapa, Pulau Kelapa Dua, dan Pulau Harapan, DKI Jakarta - Putra, Muhamad Gilang Arindra; Zamani, Neviaty Putri; Natih, Nyoman Metta N.; Yuliardi, Amir Yarkhasy (Journal of Marine and Aquatic Sciences; Vol 8 No 2 (2022), 2022)
Pollution is a threat to coral reefs in Indonesian waters. The number of coral reefs that are in very good condition denies very little compared to the total area of ??coral reefs in Indonesia. One form of pollution that can threaten coral reefs is marine debris. This study aims to identify potential sources of marine debris that can disrupt the health of coral reefs. the research was carried out in the waters of Kelapa Island, Kelapa Dua Island and Harapan Island, DKI Jakarta. The data used includes current data obtained using secondary data, data on the amount of marine debris,and the water base data substrate obtained using the LIT method. The results showed that the waste was thought to come from community activities, tourism and fisheries. The location that can be a source of marine debris in the research location comes from the mainland of Jakarta Bay. The bottom substrate conditions are in the "bad" to "medium" category. The range of the lowest proportion of live coral cover is 10,8% and the highest live coral cover at 31.1%. The coral reefs in the research location are in a state of worry  and their existence is threatened by pollution of marine debris.